FLASH dose rate helium ion beams: first in vitro investigations - Tessonnier, Thomas; Mein, Stewart; Walsh, Dietrich; Schuhmacher, Nora; Liew, Hans; Cee, Rainer; Galonska, Michael; Scheloske, Stefan; Schömers, Christian; Weber, Uli; Brons, Stephan; Debus, Jürgen; et al. (International journal of radiation oncology, biology, physics, 2021)
Purpose - To establish and investigate the effects of dose, linear energy transfer (LET), and O2 concentration on biologic response to ultrahigh dose rate (uHDR; FLASH) helium ion beams compared with standard dose rate (SDR) irradiation. - Methods and Materials - Beam delivery settings for raster-scanned helium ions at both uHDR and SDR were tuned to achieve >100 Gy/s and ∼0.1 Gy/s, respectively. For both SDR and uHDR, plan optimization and calibration for 10×10-mm2 fields were performed to assess in vitro response at an LET range of 4.5 to 16 keV/µm. Clonogenic survival assay was conducted at doses ranging from 2 to 12 Gy in 2 human lung epithelial cell lines (A549 and H1437). Radiation-induced nuclear γH2AX foci (RIF) were assessed in both epithelial cell lines and primary human pulmonary fibroblasts. - Results - Average dose rates achieved were 185 Gy/s and 0.12 Gy/s for uHDR and SDR, respectively. No differences in cellular response to SDR versus uHDR were observed for all tested doses at 21% O2, and at 2 and 4 Gy at 1% O2. In contrast, at 1% O2 and a dose threshold of ≳8 Gy cell survival was higher and correlated with reduced nuclear γH2AX RIF signal, indicating FLASH sparing effect in the investigated cell lines irradiated with uHDR compared with SDR. - Conclusions - The first uHDR delivery of raster-scanned particle beams was achieved using helium ions, reaching FLASH-level dose-rates of >100 Gy/s. Baseline oxygen levels and delivered dose (≳8 Gy) play a pivotal role, irrespective of the studied cell lines, for observation of a sparing effect for helium ions.
Gesehen am 11.12.2021